\(6,\left(3\right)=6+0,\left(3\right)=6+\dfrac{1}{3}=\dfrac{19}{3}\)
\(6,\left(3\right)=6+0,\left(3\right)=6+\dfrac{1}{3}=\dfrac{19}{3}\)
6^6+6^3*3^3+3^6/-73
N=(6^6+6^3×3^3+3^6)/-73
tính 6^6 + 6^3 x 3^3 + 3^6 / (-73)
Rút gọn: (6 ^ 6 + 2 ^ 7 * 3 ^ 6 + 2 ^ 6 * 3 ^ 7)/(4.2 ^ 3 * 3 ^ 2 * 2 ^ 2)
5) (3-1/4+2/3) - (5-1/3-6/5) - (6-7/4+3/2) 6) (6-2/3+1/2) - (5+5/3-3/2)-(3-7/3+5/2)
7) (5/3-3/7+9)-(2+5/7-2/3)+(8/7-4/3-10) 8) (8-9/4+2/7)-(-6-3/7+5/4)-(3+2/4-9/7 pls help me
N = \(\dfrac{6^6+6^3.3^3+3^6}{-73}\)
66+63 . 36+33
-73
Rút gọn :
a) 45^10 . 5^20 / 75^15
b) 6^3 + 3 .6^ 2 + 3^3 / -13
c) 4^6 .9^5 + 6^9 .120 / 8^4 .3^12 - 6^11
d) 3.11+42 / 5^3
Tính: 66+66.33+36 / -73
\(\dfrac{45^{10}\cdot5^{20}}{75^{15}}\)
\(\dfrac{6^6+6^3+3^3+3^6}{-73}\)
\(\dfrac{27^7+3^{15}}{9^9-27}\)
\(\dfrac{8^{20}+4^{20}}{4^{25}+64^5}\)